Without Russian Gas, a Sharp Recession Looms in Germany - Martin Gornig; Oliver Holtemöller; Stefan Kooths; Torsten Schmidt; Timo Wollmershäuser (Wirtschaftsdienst, 2022)
Abstract The German economy is steering through difficult waters. Tail winds from fading pandemic restrictions, supply-side bottlenecks in the aftermath of the coronavirus crisis, and shock waves caused by the war in Ukraine are dragging the economy in opposing directions. The common factor is the price-driving effect. Abruptly stopping gas deliveries from Russia to the European Union would drive the German economy into a deep recession. In this case, the accumulated loss of overall economic output would amount to 220 billion euro by the end of 2023.